Transformasi Dakwah, Pendidikan, dan Filantropi Muhammadiyah dalam Penguatan Islam Moderat di Indonesia Kontemporer - Nada Rakhima Salsabila; Arqom Kuswajono (Universitas Muhammadiyah Yogyakarta, 2025)
This article aims to examine the strategic role of Muhammadiyah in strengthening the face of moderate Islam in contemporary Indonesia. The study focuses on Muhammadiyah’s contributions in the fields of education, philanthropy, and digital da‘wah, which represent the implementation of Islam Berkemajuan within a dynamic social context. This research employs a descriptive qualitative method with a library research approach, drawing on academic literature and recent institutional documents. The findings indicate that Muhammadiyah’s educational institutions serve as strategic platforms for instilling values of religious moderation while fostering the emergence of a tolerant and inclusive generation. Meanwhile, Muhammadiyah’s philanthropic practices, particularly through LAZISMU, demonstrate humanitarian dedication that reaches across religious, ethnic, and social boundaries, thereby reinforcing the organization’s role in preserving pluralism. In the realm of da‘wah, Muhammadiyah has adaptively utilized technology and digital platforms to respond to the challenges of the information disruption era. Overall, this study affirms that despite facing the challenges of leadership regeneration and rapid social change, Muhammadiyah continues to demonstrate resilience and relevance. Through its Islam Berkemajuan approach, Muhammadiyah has succeeded in integrating normative Islamic values with contemporary needs in a contextual manner, thereby consistently positioning itself as a pioneer of inclusive, tolerant, and progressive Islam in Indonesia